Chest CT in COVID‐19 patients: A clinical need. Issue 1 (2nd January 2023) - Cao, Brooke; Iredell, Jonathan; Middleton, Peter; Young, Noel
Abstract: Introduction: The COVID‐19 pandemic caused by the coronavirus SARS‐CoV‐2 has resulted in a global healthcare crisis. The provision of computed tomography (CT) imaging services by radiology departments for COVID‐19 patients poses multiple challenges. Consequently, it is important to explore the clinical need and indications for thoracic CT and whether they subsequently alter patient management. Methods: We report our experience in this single‐centre retrospective cohort study of all confirmed COVID‐19 cases admitted during the peak of the 'Delta' variant wave in Australia, and who underwent a chest CT. Clinical indication and patient management plan pre‐ and post‐CT were ascertained. Results: A total of 92 out of 1403 patients who were admitted with COVID‐19 underwent a thoracic CT (73 CT pulmonary angiogram (CTPA), 14 CT Chest and five high‐resolution CT (HRCT) studies). 72.8% of studies were to evaluate for pulmonary emboli, 16.2% for assessment of COVID‐19 pneumonia complications, 5.4% for tuberculosis and 6.5% for other indications. 21 (23%) of these studies resulted in a change in management with two patients having a major change in management (thrombolysis, CT‐guided aspiration). Management was altered due to diagnosis of pulmonary embolism (PE), pneumonia, cryptogenic organising pneumonia and other reasons. Of 73 CTPA studies, 11 (15%) patients had evidence of PE. Conclusion: In our centre, thoracic CT in COVID‐19 patients were predominantly for the evaluation of PE with other indications being for COVID‐19 complications and other cardiopulmonary pathologies. 23% of studies subsequently altered patient management, suggesting there is good clinical need for CT chests for these indications. Abstract : Indications of CT chest in COVID‐19 patients during the Delta wave of the COVID‐19 pandemic differ from its usage during pre‐Delta wave. CT chest at our site during the Delta SARS‐CoV‐2 variant wave was predominantly for assessment of other cardiopulmonary pathologies.